The Pacific Northwest : growth of a regional identity - Gastil, Raymond D. (McFarland & Co., Publishers, 2010)
"This book describes the Pacific Northwest's search for a regional identity from the first Indian-European contacts through the late twentieth century, identifying those individuals and groups "who at least struggled to give meaning to the Northwest experience." It places particular emphasis on nineteenth-century writers and other celebrated individuals in the arts"--Provided by publisher.